“Rediseño topológico del sistema de subtransmisión de 69 kv del área de la operación de la zona I y II de EMELNORTE S.A, para mejorar los índices de calidad de energía.” - Angamarca Angamarca, José Eliberto (2023)
Determining a topological redesign of a 69 kV system that is currently radial is one of the proposals of the following development, based on three fundamental axes: Quality of technical service and product, reliability and technical losses with a technical-economic analysis that validates its implementation considering the technical-social benefits and corporate image of EMELNORTE S.A. A bibliographic search of types of topologies, parameter concepts, reliability indices of elements of subtransmission lines and substations is developed that allow determining the operating and reliability conditions of the current system. Finally, an additional S.N.I delivery point is proposed. and three 69 kV lines that contribute to forming an Open Loop topology between the substations of the Cantón de Pedro Moncayo and Cayambe. A ring-type topology between substations of the Otavalo Canton and Antonio Ante for optimal operation based on product quality, reliability and loss reduction, finally a technical-economic analysis that validates that it is a viable and sustainable project for its implementation.